Azerbaijan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues reviews economic development in Azerbaijan during 1995-99. The Azerbaijan authorities began to implement a far-reaching economic reform program in 1995. As a result, the serious macroeconomic imbalances, which plagued the economy in the early years of the transition, were largely eliminated. Both 1997 and 1998 were characterized by financial stability and strong real growth: average consumer price inflation over this period was close to zero and real GDP growth averaged 8 percent a year.